Cryptocurrency Analysis as an Investment Asset for Wiser Investment Decisions - Darmawansyah, Trisna Taufik; Aguspriyani, Yani; Raya, Fitri; Polindi, Miko (Jurnal Edukasi (Ekonomi, Pendidikan dan Akuntansi), 2024)
Business in the world of Cryptocurrency can be done in various ways, starting from coin mining (crypto mining), physical trading of crypto assets, long-term investment, crypto trading, crypto business consulting services, and so on. Because of the many business opportunities in the crypto world, the author needs to choose a crypto business that meets the criteria for a safe investment. The problem of this research is to identify and analyze factors that influence cryptocurrency investments' security and profit potential through a weighted SWOT approach. This research aims to analyze the use of weighting in a SWOT analysis of Cryptocurrency as an investment asset. The research method used is a qualitative descriptive method. This research was carried out by theoretically studying Cryptocurrency's development through documents and the cryptocurrency market. Researchers explore information obtained from expert sources through interviews. The research results show that Cryptocurrency as an investment asset has the advantage of high return potential, with a weight of 5, making it an attractive choice for investors. However, the lack of regulatory oversight and limited market liquidity are significant weaknesses, with weights of 4 and 3, respectively. The novelty of this study lies in the weighting approach in SWOT analysis, which provides a quantitative assessment of the factors influencing cryptocurrency investment. In addition, this research reveals that cryptocurrency investment from a global business perspective has yet to be widely implemented in Indonesia.